Religious Tolerance: Does Indonesian Law Really Guarantee It? - Akbar, Mar'ie Muhammad Falah (The Indonesian Journal of International Clinical Legal Education, 2021)
Legal protection given by the state of Indonesia to the followers of religion as has been stated in the first principle of Pancasila the divinity of the Almighty, in which the state of Indonesia, although not a country based on a particular religion but the state of Indonesia is a religious country, so that every adherent of religion guaranteed their rights and legally protected from all actions that harm the adherents of that religion. Legal protection has been contained in the 1945 Constitution of the State of the Republic of Indonesia in Article 28 E, 28 J and Article 29. The rights and freedom of religion may be limited to its fulfillment if it has the potential to interfere and interfere with the rights and freedoms of others. This is in accordance with the principle of harm-principle proposed by Jhon Stuart Mill and the view of Asma Jahangir who argued that the concept of restriction of religious freedom is only at the level of the external forum.